Active Botanical Biofiltration in Built Environment to Maintain Indoor Air Quality - Mannan, Mehzabeen; Al-Ghamdi, Sami G. (Frontiers in Built Environment, 2021)
The implementation of sustainable solutions for maintaining indoor air quality has become a particular concern to the building community. Research on green technologies for indoor air has highlighted the potential of active botanical biofiltration (ABB) systems, where the air is circulated through the plant root zone as well as the growing medium for maximum phytoremediation effect. ABB has been found beneficial for pollutant removal along with the potential for increasing humidity and air cooling. Assessment in laboratory condition revealed the removal efficiency of ABB systems ranged from 54% to 85% for total suspended particulate matters where gaseous pollutants such as formaldehyde and toluene removal efficiencies were 90% and over 33%, respectively, in a real environment. Moreover, the aesthetic value of ABB acts as an added benefit for positive mental effects. However, very limited data is available to date that demonstrates the pollutant removal efficiency of ABB systems in realistic indoor environments, and the mechanisms behind this emerging technology are still poorly understood. The purpose of this mini-review study is to present a quantitative assessment of the recent advancement of ABB systems and indoor air quality. Finally, the limitations of ABB systems and research gaps are highlighted for future improvement.